PROSES PENAKARAN GULA DAN PENGADUKAN KOPI PADA COFFE VENDING MACHINE MENGGUNAKAN PLC BERBASIS MIKROKONTROLER - Komara, Hafidz Hasan; Kurnia, Ahmad (Jurnal Mahasiswa Terapan; Vol 1 No 2 (2025): Jurnal Mahasiswa Terapan, 2025)
Excessive sugar consumption, especially through coffee drinks, is a major concern because it can increase the risk of health problems such as diabetes. Several countries have implemented regulations regarding the use of added sugar in drinks, including coffee, in order to reduce excessive sugar consumption. Technological innovation in coffee drink sugar mixing and measuring machines is important to maintain taste quality while reducing sugar content. This study aims to develop a sugar measuring and coffee stirring system on a microcontroller-based coffee vending machine using a PLC. The test results show that the use of a water pump helps maintain the stability of the liquid sugar discharge. The sugar dosage is regulated by time control via Arduino, with three measuring options: option 1 is equivalent to 12.8 grams (1 tablespoon), option 2 is equivalent to 19.2 grams (1 ½ tablespoons), and option 3 is equivalent to 26.8 grams (2 tablespoons). In addition, the 1-second stirring process produces optimal flavor in most of the options. This system can improve efficiency and consistency in measuring and mixing ingredients, thus supporting efforts to reduce excessive sugar consumption in coffee drinks.